The Impact of Language Policy in the Basic Education Core Curriculum in Thailand - Khattiyanant Nonthaisong; Miguel Mantero (Indonesian Journal of EFL and Linguistics, 2017)
Over the last 10 years, much research has been completed in the area of English language policy in Thailand. The majority of studies have focused on the pedagogy and methods involved in the teaching practices of Thai EFL educators at primary school level (Prapaisit de Segovia & Hardison, 2009; Tongpoon-Patanasorn, 2011) and secondary school level (Darasawang & Watson Todd, 2012; Nonkukhetkhong, Baldauf, & Moni, 2006). The present study delves deeper into teaching practices and addresses how English language policy is perceived and interpreted at the classroom level through the practices of Thai English teachers in a rural government secondary school in the northeast part of the country. To date, there is only one study which examines the impact of English language policy in the core curriculum on the teaching practices of EFL teachers at both primary and secondary school level has been completed (Fitzpatrick, 2011).In an effort to frame the present study, we apply Hornberger’s (2006) integrative framework as an attempt to support case study methodology. This approach provided us the opportunity to research “one or more instances of a phenomenon in its real-life context that reflect the perspective of the participants involved in the phenomenon” (Gall, Gall, & Borg, 2007, p. 447). And, it offered a grounded view of how this English language policy is being enacted in Thailand.